Dualisme Penyelesaian Sengketa Permohonan Informasi Publik - Kartika Widya Utama; Yudhitiya Dyah Sukmadewi (Administrative Law and Governance Journal, 2019)
Public Information Transparency after 1998 reformation has gained momentum since the issuance of Law No. 14 of 2008 concerning Transparency of Public Information. Public access to obtain information owned by the state administrative body does not always run smoothly. The role of the Administrative Court as a Judiciary that guarantees the upholding of Good Public Order Principles, especially the principle of public transparency, was tested. This article will discuss the extent of the role of PTUN in disputes over requests for public information, which in the process will also discuss the part of the Public Information Commission in requests for public information in terms of authority and competence. As a conceptual article, the conclusion that can be drawn is that the state administrative dispute procedure needs to be clearly stated, whether it is mandatory to use the procedure for requesting public information through the Public Information Commission or whether it can use a claim mechanism through the State Administrative Court. Keyword: Open Government, Administrative Court, Good Governance Principle Abstrak Keterbukaan Informasi Publik pasca reformasi semakin mendapatkan momentum semenjak diterbitkannya Undang-Undang No. 14 Tahun 2008 tentang Keterbukaan Informasi Publik. Akses masyarakat untuk mendapatkan informasi yang dimiliki oleh badan administrasi negara tidak selalu berjalan dengan lancar. Peran PTUN sebagai Badan Peradilan yang menjamin tegaknya Asas-asas Umum Ketertiban yang Baik khususnya asas keterbukaan publik pun diuji. Artikel ini akan membahas sejauh mana peran dari PTUN dalam sengketa permohonan informasi publik yang dalam prosesnya akan membahas pula mengenai peran Komisi Informasi Publik dalam permohonan informasi publik dari sisi kewenangan dan kompetensi. Sebagai artikel konseptual, kesimpulan yang dapat diambil adalah perlu ditegaskan dengan jelas prosedur sengketa administrasi negara apakah diwajibankan menggunakan prosedur permohonan informasi publik melalui Komisi Informasi Publik ataukah dapat menggunakan mekanisme gugatan melalui Pengadilan Tata Usaha Negara. Kata Kunci: Keterbukaan informasi publik, PTUN, Asas-Asas Umum Pemerintahan yang Baik